Pengaruh Kepemimpinan dan Motivasi Terhadap Kinerja Karyawan Pada PT Reksagriya Antam Jakarta Selatan - Rico Dwi Renaldi (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aims to determine how the influence of leadership and motivation on employee performance at PT Reksagriya Antam, South Jakarta. The method used by the author in this study is statistical quantitative method. Data collection used in this study included the distribution of questionnaires, observations and literature studies. Data processing techniques use validity test analysis, reliability test, data feasibility test (classical assumption), multiple regression analysis, determination coefficient analysis and hypothesis test using t and f tests. Based on the results of simultaneous test F test of (20.336) > Ftable (3.27) proved that leadership and motivation variables together have a positive and significant influence on employee performance with multiple regression equations Y = 13,660 + 0.215X1 + 0.481X2 and the value of the coefficient of determination At 0.537, it can be concluded that leadership (X1) and motivation (X2) together have an influence contribution of 53.7% on employee performance (Y).